Impactos das Mudanças no Uso e Cobertura do Solo na Produção e Exportação de Sedimentos na Bacia Hidrográfica do Alto Paranapanema - Boniolo, Vinicius Rainer (Universidade Federal de São Carlos, 2025)
Changes in land use and land cover are important drivers of environmental degradation in watershed areas, intensifying erosive processes and compromising the provision of ecosystem services that regulate water quantity and quality. This dissertation aimed to assess the impacts of such changes on sediment production and export in the Upper Paranapanema River Basin (BH-ALPA), located in the state of São Paulo, through multitemporal modeling based on four decades (1987, 1997, 2007, and 2017), spatial pattern analysis associated with different land use types, simulation of scenarios involving the restoration of Permanent Preservation Areas (APPs) and soil conservation practices, and validation of the modeled data with direct field measurements. The work was structured into three integrated chapters: a theoretical review, multitemporal modeling, and an applied evaluation in micro-watersheds with different land use matrices. Chapter 1 consisted of a literature review aimed at understanding the relationships between land use, erosive processes, and environmental management strategies in watersheds. This review discussed the main natural and anthropogenic factors driving soil degradation, with emphasis on the role of vegetation in controlling erosion. It also presented a critical analysis of the main models used to estimate erosion and sediment transport in watersheds, including empirical models (such as RUSLE) and semi-empirical/semi-distributed models (such as MUSLE, SWAT, AnnAGNPS, and SDR-InVEST), justifying the adoption of the SDR-InVEST model in this research. In Chapter 2, the model was applied to estimate sediment production and export in BH-ALPA for the years 1987, 1997, 2007, and 2017, based on land use data from the MapBiomas platform. The results indicated a significant increase in sediment export over recent decades, associated with the intensification and conversion of landscapes for agriculture. The modeling also made it possible to test scenarios of APP restoration and the implementation of conservation practices. Chapter 3 deepened the analysis of the influence of land use and land cover on water quality in four sub-watersheds with different landscape matrices: agriculture, pasture, and forest. Flow and physicochemical parameters of the water were collected over seven sampling campaigns and analyzed through descriptive, correlational, and multivariate statistical methods. The results revealed distinct patterns among land use types, with greater stability in forested areas and higher variability in intensively managed agricultural landscapes. Overall, the research highlights the importance of integrating soil conservation strategies into territorial planning in watersheds. Conservation practices, restoration of degraded areas, and the protection of APPs are shown to be essential for reducing sediment export and ensuring the maintenance of ecosystem services.
Impacts of Land Use and Land Cover Changes on Sediment Production and Export in the Upper Paranapanema River Basin
Keywords: Serviços ecossistêmicos; Erosão; Modelagem espacial; Qualidade da água; Práticas conservacionistas.; Ecosystem services; Erosion; Spatial modeling; Water quality; Conservation practices; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS